Analysis of the interrelationship between climate seasonality and respiratory diseases (Research, Society and Development, 2022)
The climate is directly associated with the transmission and aggravation of several respiratory pathologies. During the dry season, due to the fires in some Brazilian regions, increases in the exacerbation rates of asthma and COPD are evidenced. Therefore, this article aims to carry out an integrative review on the interrelationship between the seasonal climate and respiratory diseases. This is an integrative literature review carried out by means of electronic searches in the following databases: PubMed, Scielo, and VHL, in the month of August 2022, following the inclusion and exclusion criteria. The research was based on a review of 7 studies. Among the studies it was evidenced that humidity can indirectly influence morbidity and mortality from heat stress and hydration status. Low humidity is related to dehydration and worsening of pre-existing respiratory diseases, while high humidity, in severe cases, due to inappropriate heat exchange with the environment, can evolve with heat syncope, heat cramps, and exhaustion, leading to death. Heat waves are also associated with higher morbidity and mortality rates in elderly patients, due to reduced thermoregulation capacity in these patients. Thus, it is necessary to continue with new studies in order to improve the evaluation and prevention techniques of respiratory diseases, and to promote training for health professionals and the population, in order to promote integral health care and to carry out an early intervention plan.